DRY MATTER DIGESTIBILITY AND NATURAL ORGANIC MATTER MULBERRY FEED GAMAL LEAVES ON MALE GOAT CROSSBREED ETTAWA - Hasmawati Hasmawati; Husnaeni Husnaeni (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
This study aimed to test the level of dry matter and organic matter mulberry natural food and Gliricidia at Ettawa goat crossbreed (PE) males. This research was conducted in March and April 2016 in the village Ranomentaa Toari District of Kolaka. The material used is 12 PE male goats aged 4-6 months with a body weight of 10.44 ± 1.13 kg. Research compiled by complete randomized design (CRD) 3 treatments and 4 replications, P1 (100% mulberry), P2 (50% and 50% mulberry Gliricidia), P3 (100% Gliricidia). The parameters observed were dry matter intake (DMI), organic matter intake (OMI), dry matter digestibility (DMD) and organic matter digestibility (OMD). The data obtained were analyzed using ANOVA with F test (P 0.01 and P 0.05), when there is a continued effect with least significant difference test (BNT). Dry matter consumption and OMI highly significant (P 0.01), while DMD and OMD not significant (P 0.05) as a result of treatment. DMI highest average at P3 (295.41 grams), in line with the highest OMI on P3 (271.21 grams). While the percentage DMD and OMD each ranging between 39.82 to 41.23% and from 40.55 to 43.87%. The absence of the effect of treatment on DMD and OMD caused by the degradation rate of the different natural feed caused by the content of crude fiber (CF) and lignin as well as anti-nutritive substances in the forage. Based on the results of the study concluded that the DMI and the best OMI on Gliricidia, but had no effect on DMD and OMD